Problems in Modernization of Foreign Language Teacher Education in Ukraine - Гаманюк, Віта; Хорошилова, Наталія (Educational Dimension, 2015)
Hamanyuk V. A., Horoshilova N. V. Problems in Modernization of Foreign Language Teacher Education in Ukraine. The paper analyzes the actual general approach, framework programs and regulation’s papers in the field of foreign language education and training of foreign languages teachers in Ukraine. This paper summarizes the key provisions of these documents and identifies the key trends and mechanisms for the modernization of foreign language teacher education in Ukraine.